PERAN DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK (DP3A) KOTA BANDUNG TERHADAP PENYANDANG DISABILITAS KORBAN KEKERASAN SEKSUAL - Faris, Andhiya Moza; Siregar, Muhammad Yusuf Hang Tuah; Muttaqin, Muhammad Zaqi; Kania, Dede (DAS Institute, 2024)
This study explores the vulnerability of persons with disabilities to sexual violence and the critical role of government intervention in providing psychological and legal support for victims. The Women Empowerment and Child Protection Agency (DP3A) of Bandung City is tasked with addressing such cases. This research aims to analyze DP3A's role in handling sexual violence against persons with disabilities, as well as the challenges and efforts in its implementation. Using a descriptive-analytical method with an empirical juridical approach, the study reveals that DP3A plays a pivotal role through preventive and repressive measures. Preventive efforts are carried out via socialization programs, while repressive efforts include legal and psychological assistance to ensure victims’ rights are upheld. However, challenges such as the limited number of counselors remain, prompting DP3A to collaborate with disability communities and related organizations. Based on Lawrence Meir Friedman’s legal system theory, the handling of sexual violence against persons with disabilities has yet to be fully effective. DP3A’s role is hindered by a lack of disability counselors and persistent societal stigma viewing persons with disabilities as weak. To enhance DP3A’s role, it is recommended to increase the number of counselors specializing in disabilities, intensify public outreach about DP3A’s functions, and provide education to reduce stigma against persons with disabilities. These efforts aim to create a more inclusive and supportive environment for addressing cases of sexual violence involving persons with disabilities